Hartmann’s rectal stump revisited preoperative evaluation prior to reversal - Munger, Jordan Ari; Horesh, Nir; Naymagon, Steven; Bauer, Joel J. (International Surgery Journal, 2017)
Hartmann’s procedure is the gold standard surgical intervention in a variety of emergencies. Hartmann’s Reversal is a complex procedure and has high rates of intra-operative and post-operative complications. There are no clear guidelines or recommendations for pre-operative evaluation of the remnant colorectal pouch prior to restoration of intestinal continuity. We present two patients who underwent Hartmann reversal. In both cases, during pre-operative endoscopic evaluation of the Hartmann colorectal pouch, a stricture was incorrectly thought to be the pouch’s blind end and the anastomosis was formed proximal to that stricture. In case 1, a partial obstruction developed that was successfully treated with endoscopic balloon dilatation. In case 2, a complete obstruction occurred, requiring emergent re-operation with formation of a bypass around the stricture. Surgeons and gastroenterologists should be aware of this diagnostic pitfall, and consider pre-operative evaluation that includes both endoscopic and radiologic evaluation in patients being considered for reversal.